Image sampling in static telepathology for frozen section diagnosis. Issue 10 (1st October 1999) - Della Mea, V; Cataldi, P; Boi, S; Finato, N; Dalla Palma, P; Beltrami, C A
Abstract : BACKGROUND: A frozen section diagnostic service is often not directly available in small rural or mountain hospitals. In these cases, it could be possible to provide frozen section diagnosis through telepathology systems. Telepathology is based on two main methods: static and dynamic. The former is less expensive, but involves the crucial problem of image sampling. AIMS: To characterise the differences in image sampling for static telepathology when undertaken by pathologists with different experience. METHODS: As a test field, a previously studied telepathology method based on multimedia email was adopted. Using this method, three pathologists with different levels of experience sampled images from 155 routine frozen sections and sent them to a distant pathology institute, where diagnoses were made on digital images. After the telepathology diagnoses, the glass slides of both the frozen sections and the definitive sections were sent to the remote pathologists for review. RESULTS: Four of 155 transmissions were considered inadequate by the remote pathologist. In the remaining 151 cases, the telepathology diagnosis agreed with the gold standard in 146 (96.7%). There was no significant divergence between the three pathologists in their sampling of the images. Each case comprised five images on average, acquired in four minutes. The overall time for transmission was about 19 minutes. CONCLUSIONS: The results suggest that in routine frozen section diagnosis an inexperienced pathologist can sample images sufficiently well to permit remote diagnosis. However, as expected, the internet is too unreliable for such a time dependent task. An improvement in the system would involve integrated real time features, so that there could be interaction between the two pathologists.